Fluorescence Nanoscopy with Optical Sectioning by Two-Photon Induced Molecular Switching using Continuous-Wave Lasers - Fölling, Jonas (2008)
During the last decade far-field fluorescence microscopy methodshave evolved that have resolution far below the wavelength oflight. To outperform the limiting role of diffraction, all thesemethods, in one way or another, switch the ability of a moleculeto emit fluorescence. Here we present a novel rhodamine amidethat can be photoswitched from a nonfluorescent to a fluorescentstate by absorption of one or two photons from a continuous-wave laser beam. This bright marker enables strict control of on/off switching and provides single-molecule localization precisiondown to 15 nm in the focal plane. Two-photon induced nonlinearphotoswitching of this marker with continuous-wave illuminationoffers optical sectioning with simple laser equipment.Future synthesis of similar compounds holds great promise forcost-effective fluorescence nanoscopy with noninvasive optical sectioning.